Optimal utilization of geothermal heat from abandoned oil wells for power generation. (5th May 2019) - Kharseh, Mohamad; Al-Khawaja, Mohammed; Hassani, Ferri
Highlights: There is potential to optimize the utilization of geothermal for power generation. The optimal values of the selected WPs were identified. The optimal heat extraction rate was independent of the time. Abstract: Unlike other types of renewable energy, geothermal resources represent a stable energy source because they can be exploited regardless of meteorological conditions. In geothermal systems, heat is exchanged between the surrounding rock and the geofluid. Thus the energy potential strongly depends on the temperature of the geofluid, which in turn depends on the working parameters (WPs). The objective of the current work is to specify the optimal WPs (i.e., heat extraction rate, geofluid flow rate, and the temperature difference between the well inlet and outlet) in order to maximize the exploitation of the geothermal resource. The ground thermal properties, geothermal temperature gradient, and well dimensions based on realistic conditions in Qatar and neighboring countries were used to model electricity generation from a geothermal power plant. The simulation shows that the proper selection of the WPs can considerably increase the electricity generation of the power plant. Also, this work shows that the optimal WPs guaranties a sustainable utilization of geothermal sources, which means a constant electricity output of the Rankine turbine over time. For the working conditions in Qatar, it is determined that the maximum electricity generation would be 11 kW during the 25 years (analysis time). To get this maximum electricity generation, the optimal WPs should be as follows: 275 kW for heat extraction rate, 3.7–4.4 kg/s for geofluid flow rate, and 15–17 °C for the temperature difference.